Pencantuman Asas Kewajaran dalam Kontrak Standar (Perjanjian Baku) sebagai Salah Satu Upaya Melindungi Konsumen - Sentosa Sembiring (Fakultas Hukum Universitas Islam Indonesia, 1999)
To protect consumers, it is necessary to include reasonbleness principle in a standard ized contract should the principle beneglected, the contract bevoidor, atleast, judges can decide that such a contract is unen for ceable. Observing the principle, it is hoped that rights and duties of parties in the contract be balance. There isno any reason, there fore, for consumers not to comply with the contract they have concluded.